Analysis of Saving and Loan Cooperative Business Development Strategy and Sharia Financing on Interest in Becoming a Member - Selamet, Selamet; Suhartono, Suhartono (LPPM Universitas Terbuka, 2022)
The development of organizations in Indonesia is increasing rapidly in competition. One of the organizations that is growing rapidly in Indonesia is cooperatives. A competitive strategy is a formulation to increase the competitiveness of the company to create an attraction for members or consumers to buy products or services in the company to create a business development strategy. This type of research is descriptive Qualitative. Data collection techniques are carried out by means of observation, interviews, documentation, and questionnaires. data processing methods using descriptive analysis, porter's five force analysis, SWOT/SWOT Matrix analysis, Internal Factor Evaluation, and External Factor Evaluation. An alternative strategy for the company (KSPPS) BMT SM MWC NU Warureja Tegal to provide progress and business development, namely according to the explanation of the results of the SWOT diagram through point x, (KSPPS) BMT SM MWC NU Warureja Tegal is in quadrant I, That to carry out business development using an aggressive strategy, meaning a strategy to grow well, because the company has enough strength to be able to take advantage of the available opportunities. Based on the SWOT Matrix in Quadrant I, the steps that must be carried out by the company (KSPPS) BMT SM MWC NU Warureja Tegal using SO (strengths and Opportunities).